QUALITY OF CERTAIN READY - TO - EAT FISH PRODUCTS OF THE DOMESTIC TRADE - IYER, T. S GOPALAKRISHNA; VARMA, P R.G; RAO, C. C PANDURANGA; JOSEPH, K GEORGE; NAIR, T. S UNNIKRISHNAN (Fishery Technology, 2017)
Quality of 181 samples of ready-to-eat fish products comprising fried fish, fish curry and fish/prawn pickles collected from Cochin and Calicut were studied. Salmonella was absent in all the samples. V. cholerae was tested. in the samples collected. at Cochin and was absent in all the cases. Coliforms, E. coli, faecal streptococci and coagulase-positive staphylococci were present in some of the samples studied. The study indicated the necessity to improve the sanitary and hygienic conditions of the hotels engaged in the preparation of these products. The study further indicated that fried fish and fish curry shall not be served after 6 hours of their preparation. Added care is to be exercised in the selection of shrimps and fish for the preparation of pickles.